ANALISIS PERBANDINGAN PENERAPAN SELF ASESSMENT SYSTEM PRA DAN PASCA PEMBERLAKUAN PERATURAN PEMERINTAH NO. 46 TAHUN 2013 - Rachmawati Meita Oktaviani, Rr. Tjahjaning Poerwati (Universitas Pandanaran, 2015)
Taxes are a necessary part of the State. Tax implemented in the course based on the rules set by the Government. This study aims to compare the implementation of SME tax obligations before and after the imposition of Government Regulation No. 46 In 2013Comparisons were made from the standpoint of taxpayer obligations. Obligation undertakenbegin aspect of the calculation process, depositing, and reporting. The results obtained from this study is the aspect of the perceived benefits and disadvantages of SMEs by the taxpayer after the enactment of this Government RegulationKeywords: Comparison Analysis, Self Asessment System, Government Regulation No. 46In 2013